Insulin Resistance Is a Risk Factor for Overall Cerebral Small Vessel Disease Burden in Old Nondiabetic Healthy Adult Population - Yang, Xiaoli; Zhang, Shufan; Dong, Zhiyuan; Zi, Yincui; Luo, Yufan; Jin, Zhi; Shi, Lei; Li, Chen; Ren, Chuanchen; Wu, Danhong (Frontiers in Aging Neuroscience, 2019)
Background and Purpose：This study aimed to investigate whether insulin resistance (IR) was associated with overall cerebral small vessel disease (CSVD) burden, independent of other clinical risk factors in old nondiabetic healthy subjects. Methods: We recruited old nondiabetic healthy subjects with no taking any medications prospectively. The overall effect of CSVD on the brain was described by validated CSVD score. The homeostasis model assessment–estimated insulin resistance index(HOMA-IR) was used for IR estimation, and HOMA-IR ≥2.80 was defined as IR. We evaluated the association between IR and increasing severity of CSVD score by ordinal regression models, adjusted for demographics and cardiovascular risk factors. Results: Our study included 156 healthy participants. 34 showed IR, 122 showed non-IR. The mean age of the IR group was older than non-IR group(70.03± 7.30 versus 67.45 ±5.92, p=0.04), and the ratio of hypertension in IR was higher than non-IR.( 53.28% versus 82.35%, p<0.01). The distribution of lacunar, CMB, EPVS and CSVD score was different between 2 groups, but the WMH. In ordinal regression analysis, IR was positively associated with increasing severity of the total CSVD score (adjusted odds ratio 3.74, 95%CI was 1.63-5.08, and p<0.01 ) after adjusting for traditional risk factors. Furthermore, HOMA-IR levels revealed a positive dose-dependent correlation with the total CSVD score(p <0.01, p for trend <0.01). Conclusions: IR was independently associated with increasing severity of overall CSVD burden, independent of other clinical risk factors in nondiabetic healthy adult population. Furthermore, HOMA-IR level is correlated with CSVD burden in a dose-dependent manner.